Assessment of Hemostatic Profile in Neonates with Intrauterine Growth Restriction: A Systematic Review of Literature - Karapati, Eleni; Sokou, Rozeta; Iliodromiti, Zoi; Tsaousi, Marina; Sulaj, Alma; Tsantes, Andreas G.; Petropoulou, Chrysa; Pouliakis, Abraham; Tsantes, Argirios E.; Boutsikou, Theodora; Iacovidou, Nicoletta (Seminars in Thrombosis and Hemostasis, 2023)
Intrauterine growth restriction (IUGR) affects nearly 10 to 15% of pregnancies and is responsible for many short- and long-term adverse consequences, including hemostatic derangement. Both thrombotic and hemorrhagic events are described in the perinatal period in these neonates. The aim of this study was to systematically review the literature on the laboratory studies used to evaluate the hemostatic system of the IUGR small for gestational age neonate. We reviewed the current literature via PubMed and Scopus until September 2022. Following our inclusion/exclusion criteria, we finally included 60 studies in our review. Thrombocytopenia, characterized as hyporegenerative and a kinetic upshot of reduced platelet production due to in utero chronic hypoxia, was the main finding of most studies focusing on growth-restricted neonates, in most cases is mild and usually resolves spontaneously with the first 2 weeks of life. In regard to coagulation, growth-restricted newborns present with prolonged standard coagulation tests. Data regarding coagulation factors, fibrinolytic system, and anticoagulant proteins are scarce and conflicting, mainly due to confounding factors. As thromboelastography/rotational thromboelastometry (TEG/ROTEM) provides a more precise evaluation of the in vivo coagulation process compared with standard coagulation tests, its use in transfusion guidance is fundamental. Only one study regarding TEG/ROTEM was retrieved from this population, where no difference in ROTEM parameters compared with appropriate for gestational age neonates was found. Despite the laboratory aberrations, no correlation could be achieved with clinical manifestations of bleeding or thrombosis in the studies included. More studies are needed to assess hemostasis in IUGR neonates and guide targeted therapeutic interventions.
Keywords: intrauterine growth restriction; fetal growth restriction; neonates; platelets; coagulation tests; thromboelastometry; hemostatic system